2017
DOI: 10.23887/jst-undiksha.v6i2.9322
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Waktu Aging Pada Modifikasi Pori Zeolit Alam Dengan Ctabr

Abstract: Penelitian bertujuan untuk melihat pengaruh waktu aging pada sintesis material mesopori. Material mesopori hasil sintesis dikarakterisasi dengan XRD, FTIR dan fisisorpsi nitrogen. Analisis XRD menunjukkan bahwa variasi waktu aging berpengaruh pada struktur mesopori dari zeolit alam (MZ). Spektrum FTIR menunjukkan adanya silanol dan siloksan pada sampel MZ dan MMZ. Hal ini membuktikan bahwa sampel MZ dan MMZ pada semua variasi waktu aging merupakan material kaya silika. Analisis fisisorpsi nitrogen memberi info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…OP has a pore size of 1.780 nm, so it can be categorized as a microporous material, while OP-CTAB has a pore size of 2.045 nm, and it can be classified as a mesoporous material. The presence of CTAB induced the formation of mesopores that can be used for polymers and other large compounds that resulted in better particle dispersion (27). Based on the data, it can be concluded that OP has a large surface area but a microporous pore structure, while OP-CTAB has a small surface area but a mesoporous structure whereby mesopores can produce better particle dispersion than other porous structures.…”
Section: Characterization Of Op Powder and Op-ctab Using Betmentioning
confidence: 93%
See 1 more Smart Citation
“…OP has a pore size of 1.780 nm, so it can be categorized as a microporous material, while OP-CTAB has a pore size of 2.045 nm, and it can be classified as a mesoporous material. The presence of CTAB induced the formation of mesopores that can be used for polymers and other large compounds that resulted in better particle dispersion (27). Based on the data, it can be concluded that OP has a large surface area but a microporous pore structure, while OP-CTAB has a small surface area but a mesoporous structure whereby mesopores can produce better particle dispersion than other porous structures.…”
Section: Characterization Of Op Powder and Op-ctab Using Betmentioning
confidence: 93%
“…BET analysis determines the surface area and pore size, while the BJH (Barrett-Joiner-Halenda) method is used to determine the pore volume. In Based on the pore size, a porous material can be classified into three classes, namely, microporous material (pore size<2 nm), mesopores (pore size 2-50 nm) and macropores (pore size>50 nm) (27). OP has a pore size of 1.780 nm, so it can be categorized as a microporous material, while OP-CTAB has a pore size of 2.045 nm, and it can be classified as a mesoporous material.…”
Section: Characterization Of Op Powder and Op-ctab Using Betmentioning
confidence: 99%
“…Rice husk ash, bagasse ash, and natural zeolite are cheap and efficient adsorbents that were used as comparative media. Purbaningtias et al [6] have previously reported the usage of those materials to decrease the amount of acid of patchouli oil. Pore modification for those materials become an important step to increase the adsorption process.…”
Section: Introductionmentioning
confidence: 99%